Optimization of the cooking methods of stir‐fried beef by instrumental analysis. Issue 5 (27th February 2020) - Duan, Wen; Wang, Linhan; Zhang, Yuyu; Huang, Yan; Xiao, Junfei; Pu, Dandan
Abstract: The objective of this study was to optimize the cooking process of stir‐fried beef and investigate the release of taste compounds during cooking by instrumental analysis. The contents of taste compounds in stir‐fried beef were determined by high‐performance liquid chromatography. The optimum result was: beef 100 g stir‐fried 4.00 min with blending oil 25.00 g, sucrose 1.75 g and salt 2.00 g, the content of total umami components showed an increasing trend with the maximum value (2, 580.32 µg/g) at 4.00 min cooking and then decreased with the extension of time. The equivalent umami concentration of fried beef normal group (124.29 g MSG/100 g) and fried beef with spice package group (154.54 g MSG/100 g) were far higher than the control group (3.96 g MSG/100 g). It could be an effective method to optimize the cooking method by using instrumental analysis to replace or partly replace sensory evaluation. Practical applications: In this work, the cooking method of stir‐fried beef was optimized. Results elucidated that adding the spices was beneficial for improving the dish flavor. It is an innovative proposal of a good method to replace or partly replace the sensory evaluation with instrumental analysis. Further, it may provide guidance for the cooking process of stir‐fried beef.